A seismic investigation into the geometry and controls upon alluvial architecture in the Walloon Subgroup, Surat Basin, Queensland. Issue 4 (19th May 2017) - Shields, D.; Bianchi, V.; Esterle, J.
ABSTRACT: The sedimentology of the Walloon Subgroup (WSG) has been extensively studied; however, gaps exist in our understanding of the succession's alluvial architecture and the mechanisms controlling its complex internal organisation. Successful coal-seam gas development in the Surat Basin requires the construction of predictive facies models, which in turn necessitates a fulsome understanding of the geometry and controls on the spatial and temporal distribution of alluvial sub-environments. To improve our models of WSG facies, this study employs an open-source high-resolution 3D seismic dataset available on the western limb of the Surat Basin. Integration of core, wireline and seismic data has resolved the geometries of four discrete alluvial architectural elements, representing simple channel, channel belt, crevasse splay complexes and peat-mire sub-environments. Channel belts were found to be 1600–2000 m wide, simple channels 400–800 m in width and crevasse splays averaging 3.5 × 5.5 km. Coal bodies mapped from seismic attribute extractions were found to be 4.2 km 2 on average. The high-resolution dataset has also yielded insight into the geological controls governing the spatial and temporal distribution of these sub-environments, explaining, in part the mechanisms responsible for the complex internal distribution of facies within the WSG. In places within the study area, the WSG's sedimentary organisation appears to be initiated by the rejuvenation of deep-seated tectonic features, the expression of which is propagated upward via the mechanics of compensational stacking.